Fiducia e affidamento nella politica contemporanea: il caso Salvini - Lorusso, Anna Maria (Rivista Italiana di Filosofia del Linguaggio, 2020)
Through the analysis of a delimited corpus of tweets produced by Matteo Salvini during his period of government as Minister of the Interior, the contribution reflects on how today trust is politically constructed and how this is closer to a form of familiarity and confidence, than to a form of pondering. Thus the boundaries of three tangent but different categories will emerge: trust, reliability, confidence.